Gastric Floating Drug Delivery Systems: A Promising Carriers for The Delivery of Controlled Release Drugs - Mohammad Rashid Iqbal (International Journal of Life Science and Pharma Research, 2022)
Abstract: Low density systems or adaptively coordinated systems that has enough buoyancy to float on over contents of the stomach for a significant length of time without noticeably decelerating the rate of gastric emptying are known as floating systems. To accomplish stomach retention, the principle process of flotation was specifically examined in this drug delivery system. It is advantageous to construct medications in an oral sustained release gastro-retentive dose form for those that are absorbed in the upper portions of the GIT. The development of dynamically controlled systems depends on the rate at which the stomach empties. The most recent FDDS advancements are strategies to reduce the variability that lengthens the drug delivery system's retention period to more than 12 hours. This paper also contains an overview of several contemporary in-vitro methods that demonstrate the correct. This review on floating drug delivery systems (FDDS) was written with the intention of gathering the most recent research with a particular focus on the main mechanism of flotation to induce stomach retention. The most recent changes in A detailed discussion of FDDS is provided, covering the physiological and formulation factors impacting stomach retention, design methods for single-unit and multiple-unit floating systems, and their classification and formulation characteristics. The techniques used in vitro, the in vivo tests used to gauge the effectiveness and use Sharma N, Agarwal D, Gupta MK, Khinchi M. A Comprehensive Review On Floating Drug Delivery System. Int J Res Pharm Biomed Sci. 2011;2:428-41. Gohel MC, Mehta PR, Dave RK, Bariya NH. A More Relevant Dissolution Method For Evaluation Of A Floating Drug Delivery System. Diss Technol. 2004;11(4):22-5. Doi: 14227/DT110404P22. Yeole PG, Khan S, Patel VF. Floating Drug Delivery Systems: Need And Development. Indian J Pharm Sci. 2005;67:265. Mansuri R, Diwan A, Kumar H, Dangwal K, Yadav D. Potential Of Natural Compounds As Sunscreen Agents. Pharmacogn Rev. 2021;15(29):47-56. Doi: 5530/Phrev.2021.15.5. Tanvi R, Anupama D. Novel Polymeric Combinations For Gastroretentive Microspheres Of Stavudine. Int J Drug Dev Res. 2011;3:0-. Kamra M, Diwan A, Sardana S. Topical Liposomal Gel: A Review. Int J Pharm Sci Res 6. 2019;5148:2320. Pal K, Banthia AK, Majumdar DK. Preparation And Characterization Of Polyvinyl Alcohol-Gelatin Hydrogel Membranes For Biomedical Applications. AAPS Pharmscitech. 2007;8(1):21. Doi: 1208/Pt080121, PMID 17408220. Dixit N. Floating Drug Delivery System. J Curr Pharm Res. 2011;7:6-20. Sonia K, Anupama D. Microemulsion Based Transdermal Drug Delivery Of Tea Tree Oil. Int J Drug Dev Res. 2011;3:0-. Singh S, Majumdar DK. Evaluation Of The Gastric Antiulcer Activity Of Fixed Oil Of Ocimum Sanctum (Holy Basil). J Ethnopharmacol. 1999;65(1):13-9. Doi: 1016/S0378-8741(98)00142-1, PMID 10350365. Thakral S, Thakral NK, Majumdar DK. Eudragit®: A Technology Evaluation. Expert Opin Drug Deliv. 2013;10(1):131-49. Doi: 1517/17425247.2013.736962, PMID 23102011. Sungthongjeen S, Paeratakul O, Limmatvapirat S, Puttipipatkhachorn S. Preparation And In Vitro Evaluation Of A Multiple-Unit Floating Drug Delivery System Based On Gas Formation Technique. Int J Pharm. 2006;324(2):136-43. Doi: 1016/J.Ijpharm.2006.06.002, PMID 16828997. Shaha SH, Patel JK, Pundarikakshudu K, Patel NV. An Overview Of A Gastro-Retentive Floating Drug Delivery System. Asian J Pharm Sci. 2009;4:65-80. Patel N, Nagesh C, Chandrashekhar S, Jinal P, Devdatt J. Floating Drug Delivery System: An Innovative Acceptable Approach In Gastro Retentive Drug Delivery. Asian J Pharm Res. 2012;2:07-18. Shah SH, Patel JK, Patel NV. Stomach Specific Floating Drug Delivery System: A Review. Int J Pharm Tech Res. 2009;1:623-33. Burch J, Collins B. Anatomy And Physiology Of The Gastrointestinal Tract; 2021. Doi: 1093/Med/9780198833178.003.0001. Arora S, Ali J, Ahuja A, Khar RK, Baboota S. Floating Drug Delivery Systems: A Review. AAPS Pharmscitech. 2005;6(3):E372-90. Doi: 1208/Pt060347, PMID 16353995. Jiménez-Castellanos MR, Zia H, Rhodes CT. Design And Testing In Vitro Of A Bioadhesive And Floating Drug Delivery System For Oral Application. Int J Pharm. 1994;105(1):65-70. Doi: 1016/0378-5173(94)90236-4. , Chaurasia M, A, Gupta G, Valluru R. A Review On Gastric Floating Drug Delivery Systems. Vol. 4; 2016. Setthacheewakul S, Kedjinda W, Maneenuan D, Wiwattanapatapee R. Controlled Release Of Oral Tetrahydrocurcumin From A Novel Self-Emulsifying Floating Drug Delivery System (SEFDDS). AAPS Pharmscitech. 2011;12(1):152-64. Doi: 1208/S12249-010-9568-8, PMID 21181511. Prajapati S, Patel C, Patel L. Polymers For Floating Drug Delivery System. Syst Rev Pharm. 2011;2(1):1. Doi: 4103/0975-8453.83431. Kamalakkannan V, Puratchikody A, Prasanth VV, Masilamani K. Enhancement Of Drugs Bioavailability By Floating Drug Delivery System-A Review. Int J Drug Deliv. 2011;3:558. Tamizharasi S, Rathi V, Rathi JC. Floating Drug Delivery System. Syst Rev Pharm. 2011;2. Mayavanshi AV, Gajjar SS. Floating Drug Delivery Systems To Increase Gastric Retention Of Drugs: A Review. Res J Pharm Technol. 2008;1:345-8. Chandel A, Chauhan K, Parashar B, Kumar H, Arora S. Floating Drug Delivery Systems: A Better Approach. Int Curr Pharm J. 2012;1(5):119-27. Doi: 3329/Icpj.V1i5.10283. Singh BN, Kim KH. Floating Drug Delivery Systems: An Approach To Oral Controlled Drug Delivery Via Gastric Retention. J Control Release. 2000;63(3):235-59. Doi: 1016/S0168-3659(99)00204-7, PMID 10601721. Satishbabu BK, Sandeep VR, Ravi RB, Shrutinag R. Formulation And Evaluation Of Floating Drug Delivery System Of Famotidine. Indian J Pharm Sci. 2010;72(6):738-44. Doi: 4103/0250-474X.84583, PMID 21969746. Getyala A, Gangadharappa HV, Prasad MS, Reddy MP, Kumar TM. Formulation And Evaluation Of Non-Effervescent Floating Tablets Of Losartan Potassium. Curr Drug Deliv. 2013;10(5):620-9. Doi: 2174/1567201811310050013, PMID 23286884. Goole J, Vanderbist F, Amighi K. Development And Evaluation Of New Multiple-Unit Levodopa Sustained-Release Floating Dosage Forms. Int J Pharm. 2007;334(1-2):35-41. Doi: 1016/J.Ijpharm.2006.10.018, PMID 17097841. Tang YD, Venkatraman SS, Boey FY, Wang LW. Sustained Release Of Hydrophobic And Hydrophilic Drugs From A Floating Dosage Form. Int J Pharm. 2007;336(1):159-65. Doi: 1016/J.Ijpharm.2006.11.060, PMID 17194555. Amit Kumar N, Ruma M, Biswarup D. Gastroretentive Drug Delivery System: A Review. Asian J Pharm Clin Res. 2010;3:1-10. Allen L, Ansel HC. Ansel’s Pharmaceutical Dosage Forms And Drug Delivery Systems. Lippincott Williams & Wilkins; 2013. Kotreka UK, Adeyeye MC. Gastroretentive Floating Drug-Delivery Systems: A Critical Review. Crit Rev Ther Drug Carrier Syst. 2011;28(1):47-99. Doi: 1615/Critrevtherdrugcarriersyst.V28.I1.20, PMID 21395515. Soppimath KS, Kulkarni AR, Rudzinski WE, Aminabhavi TM. Microspheres As Floating Drug-Delivery Systems To Increase Gastric Retention Of Drugs. Drug Metab Rev. 2001;33(2):149-60. Doi: 1081/Dmr-100104401, PMID 11495501. Yeole PG, Khan S, Patel VF. Floating Drug Delivery Systems: Need And Development. Indian J Pharm Sci. 2005;67:265. Sato Y, Kawashima Y, Takeuchi H, Yamamoto H. In Vitro And In Vivo Evaluation Of Riboflavin-Containing Microballoons For A Floating Controlled Drug Delivery System In Healthy Humans. Int J Pharm. 2004;275(1-2):97-107. Doi: 1016/J.Ijpharm.2004.01.036, PMID 15081141. Tayade P, Kale R. A Multiple Unit Floating Drug Delivery System Of Piroxicam Using Eudragit Polymer. Indian J Pharm Sci. 2007;69(1):120. Doi: 4103/0250-474X.32124. Gökbulut E, Vural İ, Aşıkoğlu M, Özdemir N. Floating Drug Delivery System Of Itraconazole: Formulation, In Vitro And In Vivo Studies. J Drug Deliv Sci Technol. 2019;49:491-501. Doi: 1016/J.Jddst.2018.12.019. Nila MV, Sudhir MR, Cinu TA, Aleykutty NA, Jose S. Floating Microspheres Of Carvedilol As Gastro Retentive Drug Delivery System: 32 Full Factorial Design And In Vitro Evaluation. Drug Deliv. 2014;21(2):110-7. Doi: 3109/10717544.2013.834414, PMID 24028280. Zope GL, Darekar AB, Saudagar RB. Glimpse Of Floating Drug Delivery In Pharmaceutical Formulations: A Review. Res J Pharm Dosage Forms Technol. 2016;8(2):147-53. Doi: 5958/0975-4377.2016.00019.7. Vo AQ, Feng X, Morott JT, Pimparade MB, Tiwari RV, Zhang F Et Al. A Novel Floating Controlled Release Drug Delivery System Prepared By Hot-Melt Extrusion. Eur J Pharm Biopharm. 2016;98:108-21. Doi: 1016/J.Ejpb.2015.11.015, PMID 26643801. Somani VG, Shahi S, Udavant Y, Atram S, Satpute R, Shinde N. A Floating Pulsatile Drug Delivery System Based On Hollow Calcium Pectinate Beads. Asian J Pharm. 2009;3(2). Doi: 4103/0973-8398.55049. Ali J, Hasan S, Ali M. Formulation And Development Of Gastroretentive Drug Delivery System For Ofloxacin. Methods Find Exp Clin Pharmacol. 2006;28(7):433-9. Doi: 1358/Mf.2006.28.7.1003574, PMID 17003848. Xu J, Tan X, Chen L, Li X, Xie F. Starch/Microcrystalline Cellulose Hybrid Gels As Gastric-Floating Drug Delivery Systems. Carbohydr Polym. 2019;215:151-9. Doi: 1016/J.Carbpol.2019.03.078, PMID 30981340. Gupta NV, Shivakumar HG. Preparation And Characterization Of Superporous Hydrogels As Gastroretentive Drug Delivery System For Rosiglitazone Maleate. DARU J Pharm Sci. 2010;18:200-10. Zhang LP, Wang XL, Pang QQ, Huang YP, Tang L, Chen M Et Al. Solvent-Responsive Floating Liquid Crystalline-Molecularly Imprinted Polymers For Gastroretentive Controlled Drug Release System. Int J Pharm. 2017;532(1):365-73. Doi: 1016/J.Ijpharm.2017.09.008, PMID 28888975. Vedha HB, Brahma RA, Samyuktha RB. Floating Drug Delivery Of Nevirapine As A Gastroretentive System. J Young Pharm JYP. 2010;2(4):350-5. Doi: 4103/0975-1483.71622, PMID 21264092. Upadhye AA, Ambike AA, Mahadik KR, Paradkar A. Application Of Ion Exchange Resin In Floating Drug Delivery System. Drug Dev Ind Pharm. 2008;34(10):1117-24. Doi: 1080/03639040801973982, PMID 18777244. Jiménez-Castellanos MR, Zia H, Rhodes CT. Design And Testing In Vitro Of A Bioadhesive And Floating Drug Delivery System For Oral Application. Int J Pharm. 1994;105(1):65-70. Doi: 1016/0378-5173(94)90236-4. Adibkia K, Hamedeyazdan S, Javadzadeh Y. Drug Release Kinetics And Physicochemical Characteristics Of Floating Drug Delivery Systems. Expert Opin Drug Deliv. 2011;8(7):891-903. Doi: 1517/17425247.2011.574124, PMID 21506906. Singh BN, Kim KH. Floating Drug Delivery Systems: An Approach To Oral Controlled Drug Delivery Via Gastric Retention. J Control Release. 2000;63(3):235-59. Doi: 1016/S0168-3659(99)00204-7, PMID 10601721. Seth SD. Text Book Of Pharmacology. Reed Elsevier Ltd; 2005. Shah SH, Patel JK, Patel NV. Stomach Specific Floating Drug Delivery System: A Review. Int J Pharmacol Res. 2009;1(3):623-33. Thapa P, Jeong SH. Effects Of Formulation And Process Variables On Gastroretentive Floating Tablets With A High-Dose Soluble Drug And Experimental Design Approach. Pharmaceutics. 2018;10(3):161. Doi: 3390/Pharmaceutics10030161, PMID 30227678. Streubel A, Siepmann J, Bodmeier R. Drug Delivery To The Upper Small Intestine Window Using Gastroretentive Technologies. Curr Opin Pharmacol. 2006;6(5):501-8. Doi: 1016/J.Coph.2006.04.007, PMID 16890020. Arora S, Ali J, Ahuja A, Khar RK, Baboota S. Floating Drug Delivery Systems: A Review. AAPS Pharmscitech. 2005;6(3):E372-90. Doi: 1208/Pt060347, PMID 16353995. Wang YT, Mohammed SD, Farmer AD, Wang D, Zarate N, Hobson AR Et Al. Regional Gastrointestinal Transit And Ph Studied In 215 Healthy Volunteers Using The Wireless Motility Capsule: Influence Of Age, Gender, Study Country And Testing Protocol. Aliment Pharmacol Ther. 2015;42(6):761-72. Doi: 1111/Apt.13329, PMID 26223837. Feldman M, Barnett C. Fasting Gastric Ph And Its Relationship To True Hypochlorhydria In Humans. Dig Dis Sci. 1991;36(7):866-9. Doi: 1007/BF01297133, PMID 2070698. Deshpande AA, Shah NH, Rhodes CT, Malick W. Development Of A Novel Cont Rolled Release System For Gastric Retention. P Harm Res. 1997;14(6):815-9. of floating systems, and the applications of these systems are all summarised in this paper. These systems are helpful for a number of issues that arise during the creation of a pharmaceutical dosage form.